Accountants as Catalysts for Growth in the Western Balkans : Initial Assessment of SME's Financial Management and Financial Governance - World Bank Group (World Bank, Vienna, 2019)
Good financial management and financial governance is not only an imperative for the largest companies; smaller privately-owned businesses dominate economies in the Western Balkans providing most of jobs and contributing most of the value added to the economy, and so it is essential that smaller businesses with high growth potential are not constrained by poor financial management practices. The World Bank’s Center for Financial Reporting Reform (CFRR) has developed a landscape assessment approach” that aims to identify the state of financial management and financial governance practices of Micro, Small and Medium Sized Entities (MSMEs) in the Western Balkans and opportunities for improvement, building on the Report on the Observance of Standards and Codes (ROSCs) performed in the region. The landscape assessment approach has been developed by the CFRR under the Accountants as Catalysts for Growth (A4G) initiative which aims to leverage the accounting profession to support improvements in the management of the financial health of MSMEs. This work compliments the Reports on Observance of Standards and Codes (ROSCs) that have been completed by looking at non-standard aspects of financial management. Preliminary landscape assessments have been performed in Serbia and Albania; however, this work has not yet been formally reported. These preliminary assessments have been performed to test the assessment approach before a broader roll-out under the future EU-REPARIS program work as well as identify the key financial management and financial governance practices of MSMEs that need improvement, based on stakeholder observation, and consider factors that may be giving rise to such practices and possible approaches to address them. Reports for Serbia and Albania will be completed once the assessment is finalized which may include further work in both countries resulting from refinements to the assessment approach. Stakeholder observations obtained from preliminary assessment work were used to identify financial management deficiencies in MSMEs, possible causal factors, and approaches to improvement. Stakeholders identified some fundamental deficiencies in financial management and financial governance of MSMEs in Serbia and Albania that appear to be systemic and may constrain the MSME Sector’s development overall.is important to note that these are not expressed as actionable recommendations; they are offered as key themes that should be discussed by the main stakeholders to coordinate and identify agreed actions with these themes and others. A key issue identified at this initial stage of work is that approaches to address shortcomings in financial management and financial governance of MSMEs are constrained by market conditions and institutional capacity. Future work under the A4G initiative, including completing assessments in all Western Balkans countries, and developing activities to support improvements in MSME financial management and financial governance, will need to take account of the results of this preliminary assessment work.